Systematic review of the anthropometric profile of female futsal players 2010-2020 - Rossana Gomez-Campos; Ruben Vidal-Espinoza; Fredy Muñoz-Muñoz; Fernando Alvear Vasquez; Margot Rivera Portugal; Luis Urzua Alul; Jorge Mendez-Cornejo; Marco Cossio-Bolaños (PAGEPress Publications, 2023)
The objective was to summarize the scientific literature on the anthropometric characteristics of female futsal players. A systematic review documentary study was carried out. SCOPUS, PUBMED and SCIELO databases were used to search for information on primary studies related to the anthropometric profile of women's indoor soccer (elite and non-elite). The keywords used were: futsal, female, anthropometry. The range of years for the search was from 2010 to 2020. To analyze anthropometric differences, two groups were formed: group A: elite and group B: non-elite. 31 primary studies were identified, 22 (71%) in Scopus, 5 (16.1%) in PUBMED and 4 (12.9%) in SCIELO. Three publication languages were considered (English, Spanish and Portuguese) and 6 countries were identified (Brazil, Spain, Iran, Turkey, Venezuela and Italy). Players in the elite group evidenced higher weight, height, and BMI relative to their non-elite counterparts. Discrepancy in anthropometric characteristics between elite and non-elite players was verified. These results suggest that in order to participate in competitions at the highest level in women's futsal, they should have greater weight, height and BMI than their non-elite counterparts.